A conjugate gradient method with inexact line search for unconstrained optimization - Mustafa, Mamat; Mohamed, Hamoda; Mohd, Rivaie (HIKARI Ltd., 2015)
In this paper, an efficient nonlinear modified PRP conjugate gradient method is presented for solving large-scale unconstrained optimization problems. The sufficient descent property is satisfied under strong Wolfe-Powell (SWP) line search by restricting the parameter  1/ 4 . The global convergence result is established under the (SWP) line search conditions. Numerical results, for a set consisting of 133 unconstrained optimization test problems, show that this method is better than the PRP method and the FR method.